PERAN SLACK RESOURCES DAN DIVERSITAS GENDER TERHADAP KUALITAS PENGUNGKAPAN TANGGUNG JAWAB SOSIAL - Synthia Madya Kusumawati (JEMBATAN, 2019)
The purpose of this study is to examine the impact of slack resources and boards gender (female) on the quality of corporate social responsibility disclosure. This study also tests the role of the board’s feminism in a moderating relationship between slack resources and the quality of corporate social responsibility disclosure. The analysis of this study uses moderated regression analysis with unbalanced panel data. The sample consists of 140 companies which are listed in IDX and reported sustainability report for 2014-2017.The study indicates that feminism on board of directors has a positive impact on the quality of corporate social responsibility disclosure. Whereas, when the director's feminism moderates the relationship with weakened a negative impact between slack resources and the quality of corporate social responsibility disclosure. There is no relationship between the commissioner's feminism on the quality of corporate social responsibility disclosure. Feminism on commissioners does not moderate the relationship between slack resources and the quality of corporate social responsibility disclosure. This is probably because the proportion of women on the board’s structure is slightly low.